Continuous Human Height Estimation Using Millimeter Wave Radar in Home Monitoring - Li, Zihao; Yang, Zhaocheng; Chu, Ping; Zhou, Jianhua (2025 IEEE International Workshop on Radio Frequency and Antenna Technologies (iWRF&AT), 2025)
Continuous human height estimation is a critical component of health assessments and holds significant value in monitoring various health conditions. In this paper, we propose a continuous human height estimation method using millimeter-wave radar in a home environment. The core of this method involves accumulating micro-motion point clouds that accurately reflect height characteristics for continuous human height estimation from a large number of cross-time observations. Firstly, we continuously compute point clouds in two distinct states, namely dynamic and micro-motion. Secondly, we select point clouds that are indicative of height-related features from the micro-motion point clouds of a resting subject. Finally, a clustering-based method is used for height estimation. Experimental results indicate that the proposed method exhibits high consistency and a relatively low level of bias, confirming that millimeter-wave radar is capable of providing accurate and reliable height estimations during continuous monitoring.